2012
DOI: 10.1108/14714171211272216
|View full text |Cite
|
Sign up to set email alerts
|

Critical sustainability factors in industrialised building systems

Abstract: Purpose -This paper presents findings of a research study aimed at identifying critical sustainability factors for improved implementation of Industrialised Building Systems (IBS).It also highlights the importance of decision support, through the establishment of decision making guidelines, for sustainability deliverables in IBS development.Design/methodology/approach -A broad range of sustainability factors, as perceived by researchers and practitioners, are identified through a comprehensive literature study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…Thus the result of reliability test for this research, as shown in Table 4 Figure 1 meanwhile portrays the results acquired from the mean rank analysis in order to determine the priority importance ranking of each parameter addressed in this research. The mean value 4.00 represents "important" and thus the ranking of "significant" parameters for the low medium cost housing demand in Malaysia is being classified based on the mean value, which exceeds 4.00 from the standard deviation [27]. However, parameters with the same mean value are selected based on the highest standard deviation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the result of reliability test for this research, as shown in Table 4 Figure 1 meanwhile portrays the results acquired from the mean rank analysis in order to determine the priority importance ranking of each parameter addressed in this research. The mean value 4.00 represents "important" and thus the ranking of "significant" parameters for the low medium cost housing demand in Malaysia is being classified based on the mean value, which exceeds 4.00 from the standard deviation [27]. However, parameters with the same mean value are selected based on the highest standard deviation.…”
Section: Resultsmentioning
confidence: 99%
“…The data generated from questionnaire interview are analyzed through a reliability test prior to conducting a frequency analysis. The mean rank method has been used to determine ranking of each parameter involved where the most effective parameter will be determined based on mean score with value more than 4.00 [20] …”
Section: Methodsmentioning
confidence: 99%
“…The components are then positioned and assembled into structures. The production in a controlled environment able to reduce the numbers of workers involved, shorten the construction period, increase quality of buildings, reduce cost and enhance occupational health and safety [8][9][10]. With the coordination for measurement system and open building concepts, this construction technique will improve the project deliverables.…”
Section: Ibs and Modular Coordinationmentioning
confidence: 99%
“…However, open building system will also provide a high degree of design flexibility but required a maximum coordination between the designer and manufacturer [12]. Higher commitment is required in early involvement of project between key stakeholders [10].…”
Section: Ibs and Modular Coordinationmentioning
confidence: 99%
“…The developed model of decision making support in diagnosis quantifies the overall condition properly and evaluates the possible alternatives regarding selecting a solution for building improvements [23] [24]. Sustainability involves issues such as the design and management of buildings; materials performance; operation and maintenance; long-term monitoring; and the dissemination of knowledge in related technical contexts.…”
Section: Introductionmentioning
confidence: 99%